The improvement of workers efficiency through training program in foreign large enterprises: The case of LAFARGE – M’sila. - Khatim, Mohamed Laid (Dirassat Journal Economic Issue, 2021)
We aim in this article to evaluate the enhancement of capabilities of workers who have undergone a training program in Lafarge M’sila. We used a questionnaire that comprised three parts: workers’ particularities, training, and productivity capabilities handed out to 83 workers who have trained to do many tasks. Data analysis revealed that the evaluation process during training was inadequate to measure whether this program had any effect on raising productivity capabilities of the targeted population. Also, there were no incentives to be given to excelling employees to see if incentives would have changed the outcome of training. Furthermore, post-training evaluation of workers was omitted from the training agenda, such a measure would have been the main bases for compensating excelling workers. For this training program to bare its fruits, attention has to be given to workers’ incentives and post-training measures to upgrade employee’s capabilities to excel in accomplishing their tasks.